Team Effectiveness under Hierarchical Cultures: Power Distance in Far-Western Province’s Local Government - Joshi , Ammar Raj (Journal of Kathmandu BernHardt College, 2025)
This study examines how hierarchical cultural values, particularly power distance, influence team effectiveness in Nepal’s Far-Western Province’s local government institutions. Power distance—the acceptance of unequal authority—shapes communication, trust, and participation within public teams, directly affecting their social, political, economic, and systemic performance. Using a descriptive–explanatory, cross-sectional design, the study surveyed 412 local-government employees through a structured questionnaire assessing four dimensions of power distance (authority, hierarchy, prestige, social distance) and team effectiveness. Correlational and regression analyses revealed that hierarchy and privilege (fair recognition and role clarity) are the strongest positive predictors of team effectiveness, while excessive centralization of power negatively affects social cohesion and innovation. Social distance showed minimal independent influence. The findings highlight that structured hierarchy supports coordination, but participatory leadership and transparent reward systems are essential to prevent silencing effects of high-power distance. The study finds that reducing hierarchical barriers, promoting merit-based recognition, and fostering inclusive communication can significantly enhance teamwork and organizational performance in Nepal’s decentralized governance framework.